3D graphene/hydroxypropyl-β-cyclodextrin nanocomposite as an electrochemical chiral sensor for the recognition of tryptophan enantiomers. Issue 47 (1st November 2018) - Liang, Wenting; Rong, Yanqin; Fan, Lifang; Dong, Wenjuan; Dong, Qingchen; Yang, Cheng; Zhong, Zhihui; Dong, Chuan; Shuang, Shaomin; Wong, Wai-Yeung
Abstract : A novel and facile chiral sensing platform has been designed for electrochemical enantiomer recognition based on the coupling of three-dimensional-graphene with hydroxypropyl-β-cyclodextrin (3D-G/HP-β-CD). Abstract : A novel and facile chiral sensing platform has been designed for electrochemical enantiomer recognition based on the coupling of three-dimensional-graphene with hydroxypropyl-β-cyclodextrin (3D-G/HP-β-CD). The chiral platform synergistically exploits HP-β-CD as a supramolecular chiral recognizer and 3D-G as an electrochemical indicator, to recognize tryptophan (Trp) enantiomers by differential pulse voltammetry (DPV) approach with significantly discernable electrochemical signals. The different host–guest interactions ofd - andl -Trp with HP-β-CD reveal high binding affinity to targetl -tryptophan for sensing tryptophan isomers. Moreover, we found that the peak currents of the two enantiomers showed a linear response in the concentration range of 0.5–175 μM with low detection limits of 9.6 nM and 38 nM forl - andd -Trp (S/N = 3), respectively, exhibiting remarkable sensitivity, fine reproducibility as well as great stability. This process, which is the initial demonstration of cyclodextrin-functionalized 3D-G for an electrochemical chiral recognition application, provides a new strategy for enantiosensing.